Novel Ni/ZnO Nanocomposites for the Effective Photocatalytic Degradation of Malachite Green Dye - . Adnan; . Nisar; Rahim Shah; Farah Muhammad Zada; Behramand Khan; Shaukat Aziz; Najeeb Ur Rehman; Ho Soonmin; Nisar Ahmad; Mansoor Khan; . Hanzala (Civil Engineering Journal, 2024)
Water scarcity threatens human civilization because of rapid industrialization's damage to freshwater sources. Pollutants like dyes, which are frequently found in the paper, leather, food, plastics, textile, and cosmetics industries, must be removed to preserve water. In the present study, Zinc oxide nanocomposites impregnated with nickel (Ni/ZnO) were prepared using a wet impregnation technique. These novel materials were investigated for their ability to photocatalytically degrade malachite green (MG) under the irradiation of visible. The synthesized nanocomposite catalyst was characterized by various analytical techniques, including SEM, EDX, XRD, and BET methods of surface analysis, and revealed a high surface area of 192.88 m2g-1 with an average size range from 88-354 nm. EDX results showed efficient doping of Ni (28.9%). The composites were then used under the influence of a visible light source to degrade MG dye. The investigation also assessed the degradation of MG using a photo-Fenton reagent. Factors such as catalyst dosage, H2O2 levels, pH, and duration were optimized to understand their impact in both degradation studies. The synthesized catalyst showed stunning photocatalytic activities, as 99.4% of the 60 µg.ml-1of MG was degraded in 40 min with 100 mg of Ni/ZnO at pH 8. Ni/ZnO had a good application prospect for MG degrading and can be used as a potential photocatalyst. Doi: 10.28991/CEJ-2024-010-08-011 Full Text: PDF